2001
DOI: 10.1128/aem.67.5.2197-2201.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Methyl t -Butyl Ether Cometabolism at Low Concentrations by Pure Cultures of Butane-Degrading Bacteria

Abstract: Butane-oxidizing Arthrobacter (ATCC 27778) bacteria were shown to degrade low concentrations of methyl t-butyl ether (MTBE; range, 100 to 800 g/liter) with an apparent half-saturation concentration (K s ) of 2.14 mg/liter and a maximum substrate utilization rate (k c ) of 0.43 mg/mg of total suspended solids per day. Arthrobacter bacteria demonstrated MTBE degradation activity when grown on butane but not when grown on glucose, butanol, or tryptose phosphate broth. The presence of butane, tert-butyl alcohol, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 15 publications
2
41
2
3
Order By: Relevance
“…A new application area of alkane hydroxylases is the cometabolic degradation of TCE, MTBE, and related compounds by bacteria able to grow on short-chain alkanes (typically propane to pentane) [8,[116][117][118][119][120]. The propane and TCE degrading strain P. butanovora was shown to contain butane monooxygenase genes that were closely related to sMMO [33].…”
Section: Applications Of Alkane Hydroxylase Systemsmentioning
confidence: 99%
“…A new application area of alkane hydroxylases is the cometabolic degradation of TCE, MTBE, and related compounds by bacteria able to grow on short-chain alkanes (typically propane to pentane) [8,[116][117][118][119][120]. The propane and TCE degrading strain P. butanovora was shown to contain butane monooxygenase genes that were closely related to sMMO [33].…”
Section: Applications Of Alkane Hydroxylase Systemsmentioning
confidence: 99%
“…In recent years, however, several studies have shown that bacterial [1][2][3][4][5][6][7] and fungal [8] isolates are capable of breaking the ether bond of ether fuels, generating tert-butyl alcool (TBA) in the process. TBA can then be further metabolized, either by the same microorganism [2,[5][6][7] or by other microorganisms living in the same natural or artificial consortium [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…(Liu et al 2001), Pseudomonas citronellonis (Bhattacharya et al 2003), Pseudomonas oleovorans (Witholt et al 1990), Pseudomonas aeruginosa (Belhaj et al 2002), Hormoconis resinae (Solana & Gaylarde 1995), Aspergillus niger (Volke-Sepulveda et al 2003) and three bacterial enriched consortia isolated from polluted areas as described by Okeke & Frankeberger (2003).…”
Section: Introductionmentioning
confidence: 99%